KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN PADA PERUSAHAAN PROPERTY & REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2013 - Wahyudi, Dharma; Nasir, Azwir; Kurnia, Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study examined the effects of current ratio,net profit margin, debt to asset ratio, firm size, firm status, firm age and proportion of public ownership on disclosure extend of annual report. The sample of this study is 41 of Property and Real Estate Companies Listed On The Stock Exchange (BEI) during 2011-2013. Analytical techniques used to perform the hypothesis testing is purposive sampling. Data are analyzed using logistic regression method using SPSS (Statistical Product and Service Solution) 17 version. The results showed that current ratio, net profit margin, firm status, firm age and proportion of public ownership had a effect to disclosure extend of annual report. But debt to asset ratio and firm size had not effect to disclosure extend of annual report. Current ratio showed signification values 0,035. This the decision made is to accept hypothesis H1. Net profit margin showed signification values 0,024. This the decision made was to accept hypothesis H2. Debt to asset ratio showed signification values 0,518. This the decision made is to reject hypothesis H3. Firm size showed coefficient signification values 0,648. This the decision made was to reject hypothesis H4. Firm status showed signification values 0,039. This the decision made is to accept hypothesis H5. Firm age showed signification values 0,012. This the decision made is to accept hypothesis H6. And proportion of public ownership showed signification values 0,000. This the decision made is to accept hypothesis H7.Keywords: Financial statement, Property and Real Estate Companies, The Stock Exchange Of Indonesia